Automatic Building Process of Self-Closed Modified N-tree - Yibing Liu; Xiaodong Zhu; Ying Chen; Yu Li; Ning Deng (Institute of Advanced Engineering and Science, 2014)
Some features of prevailed workflow like Petri net and Grid workflow make them cannot adapt to the dynamic operation. So, we proposed a modified N-tree model to control a workflow. Modified N-tree model can remedy some problems exist in these prevailed workflow models. Firstly, we approve the proposed modified N-tree model is self-closed. This feature makes sure that this workflow can accomplish its tasks, when we change nodes of a well-running modified N-tree workflow before or while its execution. It is the prerequisite of dynamic characteristics of modified N-tree model. And, then we give a method to change this tree dynamically based on the self-closed merit. Finally, based on the dynamic characteristics of this model, we give a method to build on this N-tree workflow model automatically by using left root (LR) analysis method proposed by Mr. D.Knuth. This is the most important performance of this model. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3901